2016
DOI: 10.1007/s11081-016-9319-0
|View full text |Cite
|
Sign up to set email alerts
|

Discrete time and continuous time formulations for a short sea inventory routing problem

Abstract: We consider a fuel oil distribution problem where an oil company is responsible for the routing and scheduling of ships between ports such that the demand for various fuel oil products is satisfied during the planning horizon. The production/consumption rates are given and assumed to be constant. We provide two alternative mixed integer formulations: a discrete time model adapted from the case where the production/consumption rates are varying and a classical continuous time formulation. We discuss different e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 27 publications
0
23
0
5
Order By: Relevance
“…The Arc-Flow formulation presented in Section 3 is the one that has provided better computational results for related problems, see Agra et al [3]. Nevertheless this formulation still provides large integrality gaps which is common for continuous time models.…”
Section: Formulation Improvementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Arc-Flow formulation presented in Section 3 is the one that has provided better computational results for related problems, see Agra et al [3]. Nevertheless this formulation still provides large integrality gaps which is common for continuous time models.…”
Section: Formulation Improvementsmentioning
confidence: 99%
“…Nevertheless this formulation still provides large integrality gaps which is common for continuous time models. Agra et al [3] compared continuous and discrete time models for a maritime inventory routing problem and found that the discrete time models tended to provide better bounds, but the running times using the discrete time models were in general worse than the running times using the continuous time model. They concluded that, for the constant consumption rate case, a continuous time model with valid inequalities was the best option among all the tested ones to solve small real sized instances.…”
Section: Formulation Improvementsmentioning
confidence: 99%
“…There are a few examples in the literature for maritime inventory routing problems, though mostly in the industrial and tramp shipping (see for example [1,6,9,11,[14][15][16][17]). These literature suggest substantial financial savings by combining ship routing and scheduling planning with inventory management in industrial and tramp shipping.…”
Section: Introductionmentioning
confidence: 99%
“…Small-scale distribution of multiple oil products between islands has been studied by Agra and colleagues. Both a discrete time and a continuous time mixed integer formulation of the problem are presented in [12] and heuristic approaches for making real life problem sizes solvable are discussed in [12]. Small-scale LNG distribution differs somewhat from large-scale distribution and large-scale models are rarely adequate directly for small-scale purposes.…”
Section: Introductionmentioning
confidence: 99%